Teaching Strategies in Community Health Nursing for Undergraduate Nursing Student: An Integrative Literature Review - Lourlyn Pagonzaga Mansaguiton (Humanistic Network for Science and Technology (HNST), 2018)
This paper identified and analyzed available evidence in the literature for effective teaching strategies in Community Health Nursing (CHN) for the undergraduate nursing students. This integrative literature review was conducted in CINAHL and Google Scholar databases between August 2016 and September 2016. Since there is a paucity of articles on the area of teaching strategies for Community Health Nursing (CHN) course, inclusion criteria was liberal. Research and non-research articles published in English from 2013 to 2017 were included in the integrative literature review. Sample articles composed of one research articles and five non-research articles published between 2013 and 2017. One consistent finding in the literature is that nurse educators use simulation as a teaching strategy in CHN course. Nurse educators have used simulations with or without technology enhancement in CHN course for undergraduate nursing students. Sample articles provide benefits of using simulation, and benefits include enhancing self-confidence and competence of nursing students, providing the active-learning environment and addressing the problem of finding secured community-based sites for CHN course. Further studies with strong level of evidence on teaching strategies in CHN course for the undergraduate nursing student is recommended.Keywords: Teaching strategies, Community health nursing, Undergraduate nursing students